Thermal and Structural Behavior of Dioctadecyldimethylammonium Bromide Dispersions Studied by Differential Scanning Calorimetry and X-Ray Scattering - Feitosa, Eloi; Adati, Renata Danielle [UNESP]; Hansson, Per; Malmsten, Martin (Public Library Science, 2012)
Dioctadecyldimethylammonium bromide (DODAB) is a double chain cationic lipid, which assembles as bilayer structures in aqueous solution. The precise structures formed depend on, e.g., lipid concentration and temperature. We here combine differential scanning calorimetry (DSC) and X-ray scattering (SAXS and WAXS) to investigate the thermal and structural behavior of up to 120 mM DODAB in water within the temperature range 1-70 degrees C. Below 1 mM, this system is dominated by unilamellar vesicles (ULVs). Between 1 and 65 mM, ULVs and multilamellar structures (MLSs) co-exist, while above 65 mM, the MLSs are the preferred structure. Depending on temperature, DSC and X-ray data show that the vesicles can be either in the subgel (SG), gel, or liquid crystalline (LC) state, while the MLSs (with lattice distance d = 36.7 angstrom) consist of interdigitated lamellae in the SG state, and ULVs in the LC state (no Bragg peak). Critical temperatures related to the thermal transitions of these bilayer structures obtained in the heating and cooling modes are reported, together with the corresponding transition enthalpies.